Endocannabinoids and the Control of Energy Homeostasis - Kunos, George (American Society for Biochemistry and Molecular Biology, 2008)
Endocannabinoids (ECBs) are ubiquitous lipid mediators that act through the same G protein-coupled receptors (CB(1) and CB(2)) that recognize plant-derived cannabinoids. As regulators of metabolism, ECBs are anabolic: they increase the intake, promote the storage, and decrease the expenditure of energy. Recent work indicates that activation of peripheral CB(1) receptors by ECBs plays a key role in the hormonal/metabolic changes associated with obesity/metabolic syndrome and may be targeted for its pharmacotherapy.